Exploring the multi-stakeholder experience in Kenya. Issue 2 (2nd July 2016) - Munyua, Alice Wanjira
ABSTRACT: This paper attempts to explore the extent to which the multi-stakeholder model has contributed to the vibrant information and communications technology (ICT) sector in Kenya. It shows how stakeholder organisation and lobbying, as well as political decisions, influenced the innovation and diffusion of ICTs, and how the multi-stakeholder approach gained support from both governmental and non-governmental players in the ICT sector. The paper highlights socio-political dynamics and changes that have taken place, which have led to the multi-stakeholder approach being applied in order to develop ICT policies and create new institutions deploying infrastructure, rollout, and management. It also explores how the multi-stakeholder partnership (MSP) approach has been applied to the discussion and regulation of post-access issues. This paper is based on interviews, the author's broad experience in this area, and reviews of Kenya ICT Action Network documents, as well as mailing list discussions.